FAKTOR PENYEBAB KEMATIAN BAYI DI WILAYAH KERJA PUSKESMAS NGOMBOL KABUAPTEN PURWOREJO (STUDI KASUS TAHUN 2015) - Arinta Riza Andriani; Ayun Sriatmi; Sutopo Patria Jati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Infant mortality is infants death who aged 0 to 11 months. Infant Mortality Rate Purworejo from year to year has increased (in 2013 amounted to 11.54/1000 kh and 2014 amounted to 12.55/1000 kh), and still higher than IMR Central Java (10.41/1,000 kh). Region of Ngombol’s PHC is one areas that experienced high infant mortality and increased for 2 years. This study aims to determine direct and indirect causes of infant mortality in area of Ngombol’s PHC. Research method using qualitative descriptive which retrospective. Research sample are main informant consisted of 11 women whose babies died in 2014, and informant triangulation head of PHC, midwife coordinator, and 3 village midwife. Research variables consisted of maternal factors, infant, environmental, and health services. Direct causes of infant mortality in Ngombol region on 2014 was LBW, asphyxia and congenital abnormalities. Age of mother at risk (> 30 years) was found in maternal LBW infants and asphyxia. Almost all women had experience pregnancy complications such as hypertension, HB less, KEK. All mothers get exposure chemical smoke from her husband. Almost all informants have cage attached to house. Quality of antenatal, childbirth and neonate care still less than optimal, both in terms service providers and community. Most mothers do not know pregnant women class program because less socialization. GSIB program is not running as a cross-sectoral support is lacking. Conclusion this study is indirect causal factor of infant mortality in Ngombol region dominated by factors maternal age, pregnancy complications, environment exposure, and health services quality.